I hear you call my name and it feels like home: Right-Wing Authoritarianism and academic major choice - Gruda, Dritjon (2025)
Right-Wing Authoritarianism (RWA) is characterized by a preference for order, hierarchy, and conformity to norms, and has been associated with conservative values and structured environments. Using a sample of 5762 participants across 18 majors, we examine the association between RWA and academic college major choice, proposing that individuals with higher RWA scores are more likely to select disciplines that align with their values of structure and authority. We found that individuals with higher RWA scores were more likely to choose disciplines emphasizing authority and tradition, such as Business, Law, and Medicine. We also found a moderating effect of gender, in that men with high RWA tended to select traditionally masculine fields (e.g., Engineering and Law), while women favored caregiving-oriented majors (e.g., Psychology and Social Work), reinforcing conventional gender roles. These findings suggest that RWA influences not only political and social attitudes but also academic choices, highlighting the importance of considering personality traits in understanding educational trajectories and their broader social implications.